What does my technology facilitate`? A toolbox to help researchers understand the societal impact of a technology in the context of disasters - Lorena Daphna Kuratle; Irina Dallo; Michèle Marti; Stauffacher Michael (Seismica, 2024)
Disaster risk is increasing globally. Emerging technologies – Artificial Intelligence, Internet of Things, and remote sensing – are becoming more important in supporting disaster risk reduction and enhancing safety culture. Despite their presumed benefits, most research focuses on their technological potential, whereas societal aspects are rarely reflected. Taking a societal perspective is vital to ensure that these technologies are developed and operated in ways that benefit societies’ resilience, comply with ethical standards, are inclusive, and address potential risks and challenges. Therefore, we were particularly interested in understanding how societal impacts can be considered and leveraged throughout the development process. Based on an explorative literature review, we developed a toolbox for professionals working on emerging technologies in disaster risk reduction. By applying a Delphi study with experts on AI in seismology, we iteratively adapted and tested the toolbox. The results show that there is a need for guided reflection in order to foster discussion on the societal impacts. They further indicate a gap in the common understanding that is crucial for developing inclusive technologies or defining regulations. Our toolbox was found to be useful for professionals in reflecting on their developments and making technologies societally relevant, thereby enhancing societies’ resilience.